CPs Move Rightward, Not Leftward. (15th October 2018) - Bruening, Benjamin
Abstract: Several recent proposals hold that CP complements appear rightmost in many languages as the result of a two‐step leftward‐movement process: first the CP moves leftward, then a remnant phrase carries all other material to the left of that moved position. I show here that the arguments that have been given in favor of this approach do not go through. In contrast, a rightward‐movement analysis explains all the facts in a much simpler and less ad hoc derivation. These facts include (i) a left‐right asymmetry in syntactic category; (ii) binding facts; (iii) preposition stranding; and (iv) extraction. Importantly, binding must depend on precede‐and‐command rather than c‐command (Bruening2014 ) and there is never reconstruction for Binding Condition C. Regarding preposition stranding, the results of a large‐scale survey reveal that there is actually significant speaker variability in whether prepositions can be stranded when CPs move to the right. I spell out a nongrammatical account of this variability within the rightward‐movement analysis. With many of these phenomena, rightward movement of CPs does not pattern with remnant‐VP fronting, as it should in the leftward‐movement analysis.